The African margin of the Mozambique channel, the turbiditic system : a source to sink approach during the Meso-Cenozoic. - (:unkn) unknown (My University, 2018)
The Zambezi system located on the eastern slope of Africa is characterized by a turbiditic system of very large size (x 100 km) and is associated onshore to the third largest watershed in Africa (1,320,000 km2) after those of the Nile and Congo. Few studies have examined the evolution of the land - sea system from the eroding catchment to the sedimentation basin. This work will focus on: [1] characterize and discuss the origin of the deformations recorded in the Zambezi sedimentary system since 155 Ma, [2] quantify the erosion-sedimentation balances of the Zambezi system, for a better understanding of the sedimentary routing
Keywords: African Research